REVITALIZING RETAIL: HOW INNOVATIVE MARKETING STRATEGIES CAN TRANSFORM CONSUMER ENGAGEMENT AND ATTRACT INVESTMENT - Utari, Tituk; Tugiyono, Jentot; Togatorop, Agus Leonard; Harto, Harto; Noviany, Henny (Branding: Jurnal Manajemen dan Bisnis, 2024)
The retail industry faces major challenges from changes in consumer behavior triggered by advances in digital technology and increased access to information. Adaptation to rising consumer expectations and demand for personalized and innovative shopping experiences is crucial. The use of technology and marketing strategies that focus on data personalization is the answer to this need. This research aims to analyze how innovative marketing strategies can increase consumer engagement and attract investment in the retail sector. This research was conducted with a qualitative approach, using data from relevant previous studies and processing to understand the current dynamics in the retail industry. Data is systematically analyzed to explore how innovations in marketing influence consumer behavior and the attractiveness of the retail sector to investors. The research conclusions show that implementing innovative marketing strategies such as personalization and the use of advanced technology increases consumer engagement and loyalty. This strategy also strengthens the company's position in intense market competition. Furthermore, the innovation shows potential to improve operational efficiency and attract investment. Effective risk management and a deep understanding of investor preferences are also crucial in maximizing the benefits of innovative strategies. Overall, innovative marketing strategies have proven essential in adapting and overcoming the challenges of this digital era.